EVALUATION OF THE RELATIONSHIP GENERATED BETWEEN SERUM BIOMARKERS (HS-CRP, PLASMA FIBRINOGEN) WITH SIGNIFICANT CORONARY ARTERY DISEASE AND NUMBER OF CORONARY VESSELS INVOLVMENT - Ahmed Abdulrazaq Ali; Marwan Kamil Aboud; Zuhair Malallah Kadum (Scholar Express Journals, 2022)
Inflammation is widely considered to be an important contributing factor of the pathophysiology of coronary heart disease (CHD), and it is particularly important in the atherosclerotic process; recent work has been focused on whether biomarkers of inflammation may help to anticipate coronary artery lesions before the diagnostic coronary angiography done, hs C-reactive protein (hs-CRP) & plasma fibrinogen (PF) level has emerged as one of the most important novel inflammatory markers.
Keywords: ICHD; hs-CRP; Plasma